A checklist for trauma quality improvement meetings: A process improvement study. Issue 10 (October 2019) - O'Reilly, G.M.; Mathew, J.; Roy, N.; Gupta, A.; Joshipura, M.; Sharma, N.; Mitra, B.; Cameron, P.A.; Fahey, M.; Howard, T.; Kumar, V.; Jarwani, B.; et al.
Highlights: This was a prospective before-and-after study in four major trauma centres in India over more than one year. Data was collected at 68 Trauma Quality Improvement Meetings and the intervention was a Trauma Quality Improvement Meeting Checklist. The introduction of the Trauma Quality Improvement Meeting Checklist led to more structured Meetings. For cases brought to the Meetings, there was an increase in the discussion and agreement on preventability of death and plans for loop closure. A Trauma Quality Improvement Meeting Checklist should be considered for all centres managing trauma patients. Abstract: Background: Each year approximately five million people die from injuries. In countries where systems of trauma care have been introduced, death and disability have decreased. A major component of developed trauma systems is a trauma quality improvement (TQI) program and trauma quality improvement meeting (TQIM). Effective TQIMs improve trauma care by identifying and fixing problems. But globally, TQIMs are absent or unstructured in most hospitals providing trauma care. The aim of this study was to implement and evaluate a checklist for a structured TQIM. Methods: This project was conducted as a prospective before-and-after study in four major trauma centres in India. The intervention was the introduction of a structured TQIM using a checklist, introduced with a workshop. This workshop was based on the World Health Organization (WHO) TQI Programs short course and resources, plus the developed TQIM checklist. Pre- and post-intervention data collection occurred at all meetings in which cases of trauma death were discussed. The primary outcome was TQIM Checklist compliance, defined by the discussion of, and agreement upon each of the following: preventability of death, identification of opportunities to improve care and corrective actions and a plan for closing the loop. Results: There were 34 meetings in each phase, with 99 cases brought to the pre-intervention phase and 125 cases brought to the post-intervention phase. There was an increase in the proportion of cases brought to the meeting for which preventability of death was discussed (from 94% to 100%, p = 0.007) and agreed (from 7 to 19%, OR 3.7; 95% CI:1.4–9.4, p = 0.004) and for which a plan for closing the loop was discussed (from 2% to 18%, OR 10.9; 95% CI:2.5–47.6, p < 0.001) and agreed (from 2% to 18%, OR 10.9; 95% CI:2.5–47.6, p < 0.001). Conclusion: This study developed, implemented and evaluated a TQIM Checklist for improving TQIM processes. The introduction of a TQIM Checklist, with training, into four Indian trauma centres, led to more structured TQIMs, including increased discussion and agreement on preventability of death and plans for loop closure. A TQIM Checklist should be considered for all centres managing trauma patients.